Two new species of Pontederia L. (Pontederiaceae Kunth) to South America - Sousa, Danilo J.l.; Siqueira, Gabriela B.; Giulietti, Ana Maria (Phytotaxa, 2020)
Two new species of Pontederia are here described and illustrated. Pontederia gigantea is similar to P. sagittata by its sagittate leaf blade, but the first one presents blue flowers while the second one has whitish to pinkish flowers. Besides that, P. gigantea is endemic to Brazil, occurring in small populations through the east coast, in the Atlantic Rainforest. Meanwhile, P. sagittata occurs in the south of Mexico and Honduras. Pontederia reflexa occurs disjunctly in South America, in Northeastern Brazil, where its distribution is linked to semiarid areas; and in Bolivia, Paraguay and Brazilian Pantanal. This species is related to the whitish-flowered species of Pontederia, and is differentiated from other species of Pontederia by the reflex and revolute spathe. An updated identification key to species of Pontederia and a map showing the geographic distribution of the new taxa are also provided.